Land satellite imagery and integrated geophysical investigations of highway pavement instability in southwestern Nigeria - Ademila, Omowumi; Olayinka, Abel Idowu; Oladunjoye, Michael Adeyinka (Geology, Geophysics and Environment, 2020)
The high global numbers of road accidents due to bad roads and the failure of other engineering structures have necessitated this study, particularly as road transport accounts for a higher percentage of cargo movement in African countries. The geophysical investigation was carried out on six failed and two stable sections along the Ibadan-Iwo-Osogbo highway to examine the geological factors responsible for highway failure in the area. A Landsat ETM+ (Enhanced Thematic Mapper Plus) imagery of the study area and its environs was acquired and processed for lineaments analyses. Magnetic, Very Low Frequency Electromagnetic (VLF-EM) and electrical resistivity methods involving Schlumberger Vertical Electrical Sounding (VES) and 2-D imaging using a dipole-dipole array were utilized. Lineaments were identified across failed localities. Lateral magnetic variations in the near-surface geological materials characterized the study area. The 2-D VLF-EM models generated showed conductive zones corresponding to fractured zones of conductive clay materials within the basement rocks. Subgrade soils below the highway pavement along the failed sections are typical of incompetent clayey and sandy clay/clayey sand formations with resistivity values between 20–475 Ω∙m. In comparison, the subgrade soil beneath the stable sections has moderate to high resistivity values of 196–616 Ω∙m. 2-D resistivity structures across the failed segments identified low resistivity water-absorbing clay and lithological contacts. Water absorbing, clay enriched subgrade soils and the identified near-surface linear conductive features are the major geologic factors, and poor drainage network resulted in the highway failure. Remote sensing and geophysical investigations of the geological sequence and structures underlying the highway should be carried out before construction to effectively complement the routine geotechnical studies to ensure the sustainability of road infrastructure.